THE ROLE OF SOCIAL CONTROL AND OPTIMIZATION OF JUSTICE POLICY RESTORATIVE ON JUVENILE OFFENDING - Yuarini Wahyu Pertiwi; Ika Dewi Sartika Saimima (Jurnal Hukum dan Peradilan, 2022)
The West Java Child Special Penitentiary (LPKA) noted that in 2020 there were 241 juvenile detainees and 429 juvenile prisoners. Criminal behaviour in children is related to low social control such as attachment, responsibility, involvement, and the belief that the higher the social control, the lower the possibility of a child violating the law. The main issue in the settlement of juvenile criminal cases is the criminal justice system that does not take sides with children because the handling in this system has not implemented a restorative justice policy. Children who commit crimes ideally need to be returned to their original condition, not just punished for their actions. In fact, data on juvenile detainees and juvenile prisoners show an indication of suboptimal restorative justice policies. The purpose of this study was to determine the role of social control over children as perpetrators of criminal acts and to determine the policy of restorative justice in the process of resolving cases. This research is a descriptive study, using qualitative data analysis techniques with normative and empirical juridical approaches. The research subjects were 22 juvenile prisoners and detainees in one of the Penitentiaries of the West Java region. The results of the study indicate that social control plays a role in children as perpetrators of criminal acts, as well as the settlement of child criminal cases based on restorative justice policies, is not optimal. There are many diversion failures and a fairly high percentage of prison sentences that should be a last resort. There is also a large public stigma against the statement that children who violate the law should be imprisoned. On the other hand, trauma due to the examination process, prison life, and stereotypes as ex-convicts will greatly affect the psychological function of children. This can lead to low self-confidence, feeling worthless, and becoming the cause of recidivists because they feel unforgivable even though they have served their sentence.